Carcinoma of the Tail of the Pancreas Presenting As Acute Abdomen - Griffin, Reginald; Villas, Bruce; Davis, Cindy; Awad, Ziad T (JOP. Journal of the Pancreas, 2012)
Context Large bowel obstruction with perforation is an anomalous presentation of pancreatic tail carcinoma. Pancreatic cancer is often difficult to diagnose clinically and is especially furtive when it is located in the tail of the pancreas. Case report We describe a patient who presented with large bowel obstruction due to splenic flexure mass which proved to be due to pancreatic mucinous adenocarcinoma. Conclusions Pancreatic adenocarcinoma can rarely have the same presentation as colon cancer, and should therefore be considered in the differential diagnosis of large bowel obstruction.